(untitled) (Journal of the Bangladesh Agricultural University, 2024)
The present study focused on the use of extra-label drugs in commercial aquaculture. Data was collected through questionnaire interview with 30 drug retailers and 30 commercial aqua farmers in Mymensingh Sadar and Trishal upazila of Mymensingh district. All together 94 extra-label drugs of different groups were identified which included antibiotics, disinfectants, nutritional supplements, probiotics, gas remover and saline. Six groups of antibiotics having 10 different active compounds with 46 trade names were found in the drug retailer shops. These drugs were primarily prepared either for the use in veterinary or poultry but were found using indiscriminately in aquaculture. All these drugs were marketed by 18 companies in the study areas. It was observed that 83% drugs were not labeled for aquaculture purpose. Majority (77%) of the commercial aqua farmers used extra-label drugs in their farms and 73% of them never received any prescription from qualified personnel before use. Most of the farmers were unable to calculate appropriate doses and had no idea about risk, safety issue and toxicity reaction of using extra-label drugs. Farmers generally got suggestion from the drug retailer regarding application of drugs. The results also revealed that extra-label use of veterinary and poultry drugs in aquaculture is a common practice by commercial aqua farmers. Thus, the use of drugs in aquaculture should have a sufficient regulatory system in place. It is important to produce and use appropriate labeled drugs under a sufficient regulatory system for safe fish production in the aquaculture of Bangladesh. J Bangladesh Agril Univ 19(1): 160–167, 2021 https://doi.org/10.5455/JBAU.14479